Experimental investigation on progressive collapse performance of prestressed precast concrete frames with dry joints - Li, Zhong-Xian; Liu, Haokun; Shi, Yanchao; Ding, Yang; Zhao, Bo (Engineering structures, 2021)
•The collapse mechanisms of prestressed precast (PC) concrete structure are revealed according to quasi-static pushdown tests.•PC structure presents a different failure mode compared with cast-in-place reinforcement concrete (RC) structure.•PC structure has a higher collapse resistant capacity, and RC structure has a perfect ductility under large deformation.•The equivalent restrained stiffness acted at beam ends in the failed span in 1st story is larger than that in 2nd story.•Compared to RC structure, the effect of compressive arch action is reduced in prestressed PC structure, and the effect of tensile catenary action is strengthened. The prestressed precast concrete frame with dry joints is a novel structural system which has been proved to perform excellently under seismic loads in many researches, but its progressive collapse resistant mechanism need to be investigated further due to the discontinuity of longitudinal bars at joint interface. In this paper, quasi-static pushdown tests were conducted to investigate progressive collapse behavior of three half-scaled plane frame substructures with two stories and two spans under first-story middle column removal scenario. The specimens, including one cast-in-place concrete frame substructure and two prestressed precast concrete frame substructures, were designed according to the same design loads. The test results showed that these two types of frame structures could supply similar vertical resistances in compressive arch action (CAA) stage, while the prestressed precast structure presented a higher bearing capacity in tensile catenary action (TCA) stage, and the load-carrying ability was enhanced with the increase of steel strands area. However, the prestressed precast frame had a smaller failure displacement, which showed a lower ductility. Compared to the cast-in-place concrete frame, the prestressed precast concrete frame showed a distinct failure mode, in which there were almost no obvious cracks in beams, and no plastic hinges formed at beam ends, but a wide through crack appeared at the joint interface. The tension of steel strands decreased the CAA effect in beams, and speeded up the transformation from CAA stage to TCA stage during the progressive collapse process. This phenomenon became prompt with the increase of steel strands area. In terms of the same frame specimen, the peak value of axial compression force of beam in the second story was lower than that in the first story due to distinction of boundary conditions at beam ends in the two stories. However, the strength of steel strands of beams in both stories was fully utilized under large deformation due to a reliable tensile restrained stiffness at beam ends, leading to a similar peak tensile force at TCA stage.